Ciudades y anti-ciudades en el fin de siglo brasileño: contagio y locura colectiva en Os sertões - Javier Uriarte (Les Cahiers ALHIM)
This article complicates the common description of the Brazilian writer Euclides da Cunha as being focused on understanding only the interior parts of his country. This would imply a stark contrast to the majority of his contemporaries. Euclides’ interest in the Brazilian backlands would mean that he was not really influenced by the urban thought and by the social tensions of the city. While Euclides was actually obsessed with –and fascinated about– the sertão, and wanted to return to that space incessantly, his perspective is always that of the city: his gaze is entirely urban, infused by the transformations and tensions that Rio de Janeiro was undergoing. This is why, in his descriptions of the backlands and its people, he incorporates hygienist notions and ideas that come from the field of social psychology. Here I discuss some of the European sources that molded Euclides’ perspective, and I rethink the concepts of contagion and collective madness. Finally, I focus my analysis on the representation of Canudos as the reign of disorder and of the masses, as an aberrant and unthinkable city.